2015
DOI: 10.1007/s00128-015-1533-5
|View full text |Cite
|
Sign up to set email alerts
|

Distributions and Concentrations of Thallium in Korean Soils Determined by Single and Sequential Extraction Procedures

Abstract: The objectives of this study were to investigate the distribution of thallium in soils collected near suspected areas such as cement plants, active and closed mines, and smelters and to examine the extraction of thallium in the soils using 19 single chemical and sequential chemical extraction procedures. Thallium concentrations in soils near cement plants were distributed between 1.20 and 12.91 mg kg(-1). However, soils near mines and smelters contained relatively low thallium concentrations ranging from 0.18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Thallium concentrations in Korean soils near cement plants were distributed between 1.20 and 12.91 mg kg −1 . However, soils near mines and smelters contained relatively low thallium concentrations ranging from 0.18 to 1.09 mg kg −1 (Jin-Ho Lee et al 2015). Ores in western Małopolska contain up to 90 mg kg −1 (Zn sphalerite ores) and up to 1000 mg kg −1 of thallium (Fe marcasite ores) (Cabała 2009).…”
Section: Distribution Of Thallium In the Environmentmentioning
confidence: 99%
“…Thallium concentrations in Korean soils near cement plants were distributed between 1.20 and 12.91 mg kg −1 . However, soils near mines and smelters contained relatively low thallium concentrations ranging from 0.18 to 1.09 mg kg −1 (Jin-Ho Lee et al 2015). Ores in western Małopolska contain up to 90 mg kg −1 (Zn sphalerite ores) and up to 1000 mg kg −1 of thallium (Fe marcasite ores) (Cabała 2009).…”
Section: Distribution Of Thallium In the Environmentmentioning
confidence: 99%
“…24,25 Thus, the content of thallium in environmental systems has to be strongly regulated and controlled. A previous study 18 reviewed worldwide standards for thallium contamination levels in soil (Canada and Switzerland, 1 mg/kg); occupational exposure limits in air (Argentina, Mexico, United States, Canada, U.K., and Germany, 0.1 mg/m 3 , and Russia, 0.01 mg/m 3 ); and maximum contaminant levels in drinking water (United States, 2 mg/m 3 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lee. et al conducted a study on soil in South Korean locations and reported the estimated Tl content of 1.20-12.91 mg kg −1 in the soil near a cement industry facility, and 0.18-1.09 mg kg −1 near a smelter and mine [44]. In addition, 2.28 ± 1.39 mg kg −1 of Tl was found in rhizospheric soils near cement plants in China [45].…”
Section: Methods Validation and Quality Controlmentioning
confidence: 99%